NEMATODE SURVEY OF PLANTAIN ORCHARDS IN JATAÃ AND PEROLÃ‚NDIA - GOIÃS, BRAZIL - Hoff Brait, Victor Hugo Assis; Carneiro, Luciana Celeste; Ferreira, Paulo Afonso (REVISTA DE AGRICULTURA, 2020)
Banana is an important fruit for Brazil, it is the most purchased in natura. Unfortunately, as every cultivated plant, banana trees have their yield-limiting pests and diseases. Among the most detrimental are the nematodes, which are sadly also ubiquitous in banana producing areas. In JataÃ and PerolÃ¢ndia (GO) there is few data regarding the genera and population densities of plant parasitic nematodes in banana orchards. Therefore, a survey from 17 orchards is presented in this paper. All of them had plantains (AAB) planted, since it is the prevalent cultivated genetic group in the region. The nematode extraction method consisted in sieving followed by centrifugal separation. Together with the nematode survey a poll was presented to farmers, which encompassed questions about the general orchard management. Helicotylenchus was the prevailing genus in all samples. Meloidogyne and Pratylenchus also presented high population density in some areas.